PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KLAIMEN PADA PT JASA RAHARJA PERWAKILAN SURAKARTA - Luluk Takarii Sarjana Rini; Retnoningrum Retnoningrum; Legowo Dwi Resihono; Anifa Nurjanah (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine whether the service quality variables (tangible, reliability, responsiveness, assurance and sure, empathy) affect customer satisfaction at PT Jasa Raharja Representative Surakarta. This research is a survey research with data collection through questionnaires. The population in this study are customers who make claims at PT Jasa Raharja Representative Surakarta, sampling using simple random sampling, amounting to 75 respondents. The data used are primary data and secondary data. The results of this study indicate that the service quality variables on the dimensions of tangible, responsiveness, assurance and empathy have no effect on customer satisfaction. While the service quality variables on the dimensions of reliability and empathy affect customer satisfaction. The independent variables simultaneously influence customer satisfaction at PT Jasa Raharja Representative Surakarta Keywords : service quality, customer satisfaction, customer claims.